Bent Intramedullary Femoral Nail: Surgical Technique of Removal and Reconstruction - Vasileios I. Sakellariou; Stamatis Kyriakopoulos; Helias Kotoulas; Ioannis P. Sofianos (Case Reports in Orthopedics)
A secondary high-velocity trauma to a previously stabilized femoral fracture with intramedullary nailing is rare. In this paper, we present the management of a 40-year-old man presented with a bent intramedullary nail due to secondary trauma. A lateral longitudinal femoral osteotomy was used for the resection of the distorted nail. The femur was reconstructed with a new nail, and the fixation of the osteotomy was achieved with plate and cerclage wires. Five months postrevision surgery, callus formation was evident and the patient regained a normal range of motion and gait, walking with a single cane.